Fornix transected macaques make fewer perseverative errors than controls during the early stages of learning conditional visuovisual discriminations [corrected]. - Kwok, S; Buckley, M (2009)
Previous studies with macaque monkeys have found rapid learning to be impaired in both spatial (visuospatial) and non-spatial (visuomotor) associative learning tasks after fornix transection. In order to test theories that posit a general role for the fornix in associative learning, we investigated whether monkeys with fornix transection would also be impaired in the rapid acquisition of visuovisual conditional associations. We trained monkeys, postoperatively, on three sets of conditional stimulus-stimulus concurrent associations. Fornix transection did not impair learning of these associations, even in the early stages; to the contrary, animals with fornix transection made significantly fewer perseverative errors during the initial acquisition stages. These results challenge the idea that the hippocampal system plays a general role in the rapid acquisition of all kinds of associative knowledge. We suggest that the lower error rate in the early stages of the non-spatial task in the fornix transected animals may be secondary to an impairment in visuospatial processing; this might act to bias animals away from attempts to learn about spatial strategies for solving novel tasks. Additionally, we observed that fornix transected and control monkeys adopted a Change-shift response strategy in this task; the use of which was found to be fornix independent.